2017
DOI: 10.1371/journal.pone.0181127
|View full text |Cite
|
Sign up to set email alerts
|

Obesity/Type II diabetes alters macrophage polarization resulting in a fibrotic tendon healing response

Abstract: Type II Diabetes (T2DM) dramatically impairs the tendon healing response, resulting in decreased collagen organization and mechanics relative to non-diabetic tendons. Despite this burden, there remains a paucity of information regarding the mechanisms that govern impaired healing of diabetic tendons. Mice were placed on either a high fat diet (T2DM) or low fat diet (lean) and underwent flexor tendon transection and repair surgery. Healing was assessed via mechanical testing, histology and changes in gene expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
0
33
1
Order By: Relevance
“…Despite the well‐known complications that arise during diabetic tendon healing, there are few animal studies that examine the mechanisms and cell types involved in the abnormal healing response (Table ). Similar to what is seen in clinical cases of T2DM tendon injury, T2DM rodent models exhibit impaired tendon healing . More specifically, using the DIO mouse model, David et al reported increased extracellular matrix disorganization, limited tenocyte migration, and impaired biomechanical properties following a biopsy punch injury to the FDL mid‐substance.…”
Section: Diabetic Tendon Healingmentioning
confidence: 77%
See 2 more Smart Citations
“…Despite the well‐known complications that arise during diabetic tendon healing, there are few animal studies that examine the mechanisms and cell types involved in the abnormal healing response (Table ). Similar to what is seen in clinical cases of T2DM tendon injury, T2DM rodent models exhibit impaired tendon healing . More specifically, using the DIO mouse model, David et al reported increased extracellular matrix disorganization, limited tenocyte migration, and impaired biomechanical properties following a biopsy punch injury to the FDL mid‐substance.…”
Section: Diabetic Tendon Healingmentioning
confidence: 77%
“…More specifically, using the DIO mouse model, David et al reported increased extracellular matrix disorganization, limited tenocyte migration, and impaired biomechanical properties following a biopsy punch injury to the FDL mid‐substance. We recently reported that FDL tendons from DIO T2DM mice heal with an amplified fibrotic response characterized by increased expression of Col1 , collagen type 3 ( Col3 ), Mmp9 , and Mmp2 , impaired range of motion, and increased gliding resistance following transection and repair, compared with mice fed a low‐fat diet . Importantly, we also observed alterations in macrophage polarization including increased and prolonged markers of M2 macrophage activity, suggesting that aberrant activity of these cells may be critically involved in fibrotic T2DM tendon healing.…”
Section: Diabetic Tendon Healingmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, we observed a higher abundance of M1 macrophage phenotype in healthy sites of patients with T2DM compared to healthy sites in non-diabetes patients. Macrophage-mediated regulation of chronic inflammation and especially M1 polarization plays a key role in the pathogenesis of diabetic complications (32,33), and may explain the higher susceptibility of these individuals to periodontitis. These findings were corroborated by the ex vivo blood monocyte data indicating transcriptional changes in circulating blood monocytes of patients with T2DM versus non-diabetes individuals even before the cells reside in the gingival tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Only female C57Bl/6J mice were used, while male and female S100a4 GFP/+ and WT used in equal proportions across genotypes. At 10-12 weeks of age, mice underwent surgical transection and repair of the flexor digitorum longus (FDL) tendon in the hind paw as we have previously described 4,10-14 . Briefly, the distal FDL tendon was exposed and transected; two horizontal 8-0 sutures were placed in the intact tendon ends and the tendon was sutured to approximate an end-to-end repair.…”
Section: Methodsmentioning
confidence: 99%